The Embodied World: Creation Metaphors in the Ancient Near East - Simkins, Ronald A. (Biblical theology bulletin, 2014)
An insight from anthropology is that the human body may serve as a symbol of society. In the ancient Near East, including in Israel, the body mediated symbolic relationship between of people's experience of their physical and social worlds. This essay will argue that that this complex symbolic relationship between the body and the world formed the basis of the ancient Near Eastern understanding of creation. Because the body functioned as a model for the world, the procreation of the human body (microcosm) offered an appropriate analogy for understanding the creation of the world and society (macrocosm). The essay will focus on a variety of creation metaphors from Mesopotamia, Egypt, and Israel to construct a heuristic model of creation that will delineate the symbolic relationship between the body and the world.